Pengembangan Media Puzzle Kartu Gambar dengan Teknik Make A Match Pada Mata Pelajaran Tematik - Muthmainnah; Amrullah Mahmud; Arifin Dia (STKIP Andi Matappa Pangkep, 2023)
This research is based on the problems found at SDN 18 Tumampua I, namely teachers still use the lecture method and the lack of use of learning media. From the existing problems, picture card puzzle media was developed using the make a match technique with the aim of (1) producing picture card puzzle media for class II thematic learning (2) finding out valid, practical and effective puzzle media for use in class II thematic learning. This type of research is R&D using the ADDIE model. Validation was carried out by 2 validators, material experts and media experts, and tested on class II students. The validation results on puzzle learning media by material experts obtained 92% very valid criteria, media experts obtained 87% very valid criteria. Based on the results of assessing student responses from 27 students, the number of students received 92% of the very practical criteria, and the assessment of the teacher's responses received 100% of the very practical criteria. The assessment results for media effectiveness were obtained using pre-test and post-test on students using the n-gain test and obtained a score of 0.75 with very high criteria seen from the results of increasing student scores.